Phase transitions in TbMnO3 manganites - Dyakonov, V.; Varyukhin, V.; Zarzycki, A.; Dyakonov, K.; Bażela, W.; Kravchenko, Z.; Szewczyk, A.; Zubov, E.; Szymczak, R.; Szytu╕a, A.; Szymczak, H. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
X-ray diffraction and magnetic measurements of polycrystalline and nanosize TbMnO3 manganites have been performed. All the compounds studied crystallize in the orthorhombic crystal structure (space group Pnma) at room temperature. The nanosize manganites were synthesized with a sol-gel method at different (800 and 900°C) temperatures. The average size of synthesized nanoparticles (from 45 to 70 nm) was estimated by using the x-ray diffraction and low-temperature adsorption of argon methods. An information on the evolution of properties of TbMnO3 with changing grain size, temperature and magnetic field was obtained. The crystal structure parameters of nanospecimens change slightly with changing the nanoparticle size. The peculiarities of magnetic ordering in polycrystalline and nanosize TbMnO3 were compared. Magnetization and the Nèel temperature corresponding to antiferromagnetic ordering of the Tb3+ sublattice decrease as the particle size is reduced. The inverse magnetic susceptibility of the nanoparticle samples deviates from the Curie–Weiss law below 50 K, that is connected with the magnetic ordering of the Mn3+ moments. Specific heat of the nanosize samples exhibits anomalies related to the magnetic ordering of the Tb3+ and Mn3+ sublattices.